2018
DOI: 10.3847/1538-4357/aadfee
|View full text |Cite
|
Sign up to set email alerts
|

The Missing Satellites of the Magellanic Clouds? Gaia Proper Motions of the Recently Discovered Ultra-faint Galaxies

Abstract: According to LCDM theory, hierarchical evolution occurs on all mass scales, implying that satellites of the Milky Way should also have companions. The recent discovery of ultra-faint dwarf galaxy candidates in close proximity to the Magellanic Clouds provides an opportunity to test this theory. We present proper motion (PM) measurements for 13 of the 32 new dwarf galaxy candidates using Gaia data release 2. All 13 also have radial velocity measurements. We compare the measured 3D velocities of these dwarfs to … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

26
200
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 169 publications
(230 citation statements)
references
References 68 publications
26
200
4
Order By: Relevance
“…In Kallivayalil et al (2018), it was found that Hydra 2, Draco 2 and Phoenix 2 may also be associated with the MCs. Thus, we additionally include these three UFDs in our sample.…”
Section: Sample Selectionmentioning
confidence: 99%
See 3 more Smart Citations
“…In Kallivayalil et al (2018), it was found that Hydra 2, Draco 2 and Phoenix 2 may also be associated with the MCs. Thus, we additionally include these three UFDs in our sample.…”
Section: Sample Selectionmentioning
confidence: 99%
“…Nearly 30 new dwarf galaxies have recently been discovered in the vicinity of the Magellanic Clouds (MCs; Bechtol et al 2015;Drlica-Wagner et al 2015;Koposov et al 2015b;Martin et al 2015;Laevens et al 2015;Drlica-Wagner et al 2016;Torrealba et al 2016aTorrealba et al ,b, 2018Koposov et al 2018;Homma et al 2018). Furthermore, the timely second data release from the Gaia mission (Gaia Collaboration et al 2018a) has enabled proper motion (PM) measurements for these ultra-faint satellites (Simon 2018;Fritz et al 2018;Kallivayalil et al 2018;Pace & Li 2019;Massari & Helmi 2018), now making it possible to study their 3D kinematics and orbital histories in unprecedented detail. With this new data from Gaia DR2, several authors have aimed to identify the subset of known UFDs and classical dwarf spheroidals in the MW's halo that were originally satellites of the MCs.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…From an observational perspective, the past decade has witnessed the discovery of many new structures around the MCs, including a slew of 'ultra-faint' dwarfs likely to be associated to the MCs (Drlica-Wagner et al 2015;Koposov et al 2015;Deason et al 2015;Drlica-Wagner et al 2016;Jethwa, Erkal & Belokurov 2016;Sales et al 2016;Conn et al 2018;Kallivayalil et al 2018;); a 'stellar cloud' within the LMC tidal radius (Mackey et al 2016); SMC structures such as the SMCNOD that could owe to a primordial SMC satellite in advanced stage of disruption (Pieres et al 2017) and the shell-like overdensity studied by Martinez-Delgado et al (2019) that could owe to a recent star formation event triggered by interactions between the MCs and/or the MW; and the very extended, low-density, envelope of stellar material with a disturbed shape around the LMC (Nidever et al 2019). All of these structures can be used as tracers of the gravitational interaction history of the MCs .…”
Section: Introductionmentioning
confidence: 99%